2015
DOI: 10.2494/photopolymer.28.663
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Ablation in Resists and Block Copolymers for High Resolution Lithographic Patterning

Abstract: Previously, we demonstrated an all dry, selective laser ablation development in methyl acetoxy calixarene (MAC6) which produced high resolution (15-25 nm half-pitch), high aspect ratio features not achievable with wet development. In this paper, we investigate the selective laser ablation process as a means to create a block copolymer derived lithographic pattern through the selective removal of one block. Two block copolymer systems were investigated PS-b-PHOST, and P2VP-b-PS-b-P2VP. The selective laser ablat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Thus, depending on the thickness of the resist, a minimum bias voltage has to be applied to prevent mechanical tip-resist interactions. (iv) Since the tip-surface distance is significantly smaller than the mean free path (MFP) of the electrons in ambient conditions (~340-570 nm [63][64][65][66]), vacuum conditions are not required. (v) The application of low energy electrons < 100 eV, which enlarge the de Broglie wavelength (30 eV → 0.224 nm vs. 30 keV → 0.007 nm), do not affect resolution in lithographic applications.…”
Section: The Principle Of Exposure With Low-energy Electrons Using a ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, depending on the thickness of the resist, a minimum bias voltage has to be applied to prevent mechanical tip-resist interactions. (iv) Since the tip-surface distance is significantly smaller than the mean free path (MFP) of the electrons in ambient conditions (~340-570 nm [63][64][65][66]), vacuum conditions are not required. (v) The application of low energy electrons < 100 eV, which enlarge the de Broglie wavelength (30 eV → 0.224 nm vs. 30 keV → 0.007 nm), do not affect resolution in lithographic applications.…”
Section: The Principle Of Exposure With Low-energy Electrons Using a ...mentioning
confidence: 99%
“…Figure 16 shows a positive tone exposure at ambient conditions. The role of OH groups is evident [63]. Exposures in a vacuum induces negative tone behavior, which requires a wet development step.…”
Section: Influence Of the Environmentmentioning
confidence: 99%
“…Furthermore, the modification of the phenolic group to introduce metal or oxide precursors can result in a robust hard mask that can be used for subsequent pattern transfer to the underlying substrate. By utilizing protected or deprotected phenol groups, a variety of nanopatterning strategies that combine top-down and bottom-up approaches are possible. , For example, Du et al demonstrated photo-cross-linking P­(4HS) block in phase-separated P­(4HS- b -α-methylstyrene) thin film with multifunctional cross-linkers resulting in a negative tone photoresist . Hence, 4HS here not only drives phase segregation due to its high polarity, but also undergoes a photochemical reaction, leading to a patternable BCP.…”
mentioning
confidence: 99%